Spatial Wage Curves for Formal and Informal Workers in Turkey - Badi H. Baltagi; Yusuf Soner Baskaya (Institute of Labor Economics (IZA), 2022)
This paper estimates spatial wage curves for formal and informal workers in Turkey using individual level data from the Turkish Household Labor Force Survey (THLFS) provided by TURKSTAT for the period 2008-2014. Unlike previous studies on wage curves for formal and informal workers, we extend the analysis to allow for spatial effects. We also consider household characteristics that would affect the selection into formal employment, informal employment, and non-employment. We find that the spatial wage curve relation holds both for formal and informal workers in Turkey for a variety of specifications. In general, the wages of informal workers are more sensitive to the unemployment rates of the same region and other regions than formal workers. We find that accounting for the selection into formal and informal employment affects the magnitudes but not the significance of the spatial wage curves for the formal and informal workers with the latter always being larger in absolute value than that for formal workers.
Keywords: C21; J30; J60; 330; spatial wage curve; spatial weights; regional labor markets; informal labor markets